A Poet in Scientist’s Uniform: Leopold Senghor - Iryna Satygo (Pitannâ Lìteraturoznavstva)
The article is devoted to the study of the scientific views of Leopold Senghor (1906–2001), the Senegalese poet, thinker and statesman, the president of Senegal (1960–1980), a member of the French Academy (1983), the most influential writer of the West-African literary region, on the figurativeness and rhythmics of the African poetical tradition.The article emphasizes on therhythmic images, including “analogical images” and a special African rhythm – tetrameter as a specific feature of the West-African folk poetry. It is shown that the ternary African rhythms during the song performance of traditional verses create a “silent” basic rhythm, a missed sign of traditional African singing poem. It is also stressed that Senghor’s Négritude conception became an important culturological paradigm for the African poetry of the XX century. One of the basic principles of the Négritude was proclaimed the return to the African sources, and consequently, traditional African values, became source of inspiration of the African artists. It is confirmed that the rhythm acts the major part in the communication of the Africans and immanently exists in all African culture. Négritude’s existentials as rhythm and analogical image were reasoned by Senghor as the main features of the African culture.